Experimental and Applied Mechanics, Volume 4 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Sciammarella, Cesar; Considine, John; Gloeckner, Paul (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
Experimental and Applied Mechanics, Volume 4 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the fourth volume of nine from the Conference, brings together contributions to important areas of research and engineering.  The collection presents early findings and case studies on a wide range of topics, including: Advanced Methods for Frontier Applications, Non-Homogeneous Parameters Identification, Teaching Experimental Mechanics in the 21st Century, Material Characterization and Testing, Mechanics of Interfaces Novel Applications of Experimental Mechanics.